2012
DOI: 10.1155/2012/987517
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neurotoxic Secretory Phospholipases A2Enzymatic, Edematogenic, and Myotoxic Activities by Harpalycin 2, an Isoflavone Isolated fromHarpalyce brasilianaBenth

Abstract: Secretory phospholipases A2 (sPLA2) exert proinflammatory actions through lipid mediators. These enzymes have been found to be elevated in many inflammatory disorders such as rheumatoid arthritis, sepsis, and atherosclerosis. The aim of this study was to evaluate the effect of harpalycin 2 (Har2), an isoflavone isolated from Harpalyce brasiliana Benth., in the enzymatic, edematogenic, and myotoxic activities of sPLA2 from Bothrops pirajai, Crotalus durissus terrificus, Apis mellifera, and Naja naja venoms. Har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In fact, the anti-inflammatory properties of BV samples from different origins such as Egypt (Amin and Abdel-Raheem, 2014), Korea (Park et al, 2007;Park et al, 2008;Lee et al, 2009), USA (Chang and Bliven, 1979) and even commercial samples (Jang et al, 2005;Moon et al, 2007;Yoon et al, 2008) have been reported in apitherapy. Furthermore, BV individual compounds have also shown the same properties, as in the case of mast cell degranulating peptide (Banks et al, 1990), MEL (Moon et al, 2006;Park et al, 2007;Srivastava et al, 2012;Rayahin et al, 2014) and PLA2 (Ximenes et al, 2012), which are related with their capacity to reduce pro-inflammatory cytokines such as tumor necrosis factor (TNF-α) and interleukins (IL-In the present work, five bee venom samples obtained from Apis mellifera iberiensis from the Northeast Portugal were chemically characterized and evaluated for their antioxidant, antiinflammatory and cytotoxic properties.…”
Section: Introductionmentioning
confidence: 93%
“…In fact, the anti-inflammatory properties of BV samples from different origins such as Egypt (Amin and Abdel-Raheem, 2014), Korea (Park et al, 2007;Park et al, 2008;Lee et al, 2009), USA (Chang and Bliven, 1979) and even commercial samples (Jang et al, 2005;Moon et al, 2007;Yoon et al, 2008) have been reported in apitherapy. Furthermore, BV individual compounds have also shown the same properties, as in the case of mast cell degranulating peptide (Banks et al, 1990), MEL (Moon et al, 2006;Park et al, 2007;Srivastava et al, 2012;Rayahin et al, 2014) and PLA2 (Ximenes et al, 2012), which are related with their capacity to reduce pro-inflammatory cytokines such as tumor necrosis factor (TNF-α) and interleukins (IL-In the present work, five bee venom samples obtained from Apis mellifera iberiensis from the Northeast Portugal were chemically characterized and evaluated for their antioxidant, antiinflammatory and cytotoxic properties.…”
Section: Introductionmentioning
confidence: 93%
“…Some studies performed with sPLA2 from Crotalus durissus ssp. showed that the calcium binding loop is involved in the pharmacological activity [57], and others performed by [52] showed that regions close to the active site of sPLA2 could also be involved. According to [54], the C-terminal region could also participate in the interaction with pharmacological receptors.…”
Section: "To Be or Not To Be" Enzymatically Active Important For Cdt mentioning
confidence: 98%
“…Subsequently, several works with purified Lys49 basic sPLA2 from snake (Bothrops sp.) were able to induce several pharmacological activities, such as pronounced edema, myonecrosis, oxidative stress, nephrotoxicity, insulin degranulation, and anticoagulant activity [17,[48][49][50][51][52]. In the case of the sPLA2 from Cdt, it was observed that its enzymatic activity can be practically abolished through treatment with certain compounds.…”
Section: "To Be or Not To Be" Enzymatically Active Important For Cdt mentioning
confidence: 99%
See 1 more Smart Citation
“…Two polyphenolic compounds, harpalycin and quercetin, were isolated from the H. brasiliana leaves (Silva et al, 1999). These compounds have numerous biological activities in animal cells, such as free radical scavenging properties and antioxidant and anticholinesterase activities Silva et al (1997) 3-hydroxy-4-isopentenyl-8,9-methylenedioxypterocarpan Silva et al (1999 3β-hydroxy-20(29)-lupen-28-oic acid or betulinic acid Silva et al (1997;1999) Leaves Harpalycin and quercetin 5,7,3′,4′-tetrahydroxyflavonol Silva et al (1999) Roots Leiocarpin, medicarpin, maackiain, cabenegrin A-I and cabenegrin A-II Militão et al (2007) (-)-2-geranyl-3-hydroxy-8,9-methylenedioxypterocarpan Vieira et al (2008) Roots (-)-6aR,11aR-2(4′,5′-dihydroxy-1′-isopentenyl)-3-hydroxy-8,9-methylenedioxypterocarpan and (-)-6aR,11aR-2(4′-hydroxy-1′-isopentenyl)-3-hydroxy-8,9-methylenedioxypterocarpan Araújo et al (2008) 2-Geranyl-2,3′,4,4′-tetrahydroxychalcone Vieira et al (2008) Araújo et al (2008) activities (Djeridane et al, 2006;Katalanić et al, 2010;Ximenes et al, 2012). Although few studies have been performed on this plant to date, the results show that H. brasiliana is a source of several bioactive compounds of medicinal interest.…”
Section: Introductionmentioning
confidence: 99%